Resultados preliminares sobre o efeito da profundidade de plantio na emergência e em algumas características agronômicas da soja (Glycine max (l.) Merril) - Vasconcelos Costa, Alberto; Sediyama, Tuneo; Nogueira Fontes, Luiz Antônio (Revista Ceres, 2025)
This paper presents the results of an exploratory study on the effect of planting depth on soybean seedling emergence and some plant characteristics, carried out in Viçosa and Capinópolis, State of Minas Gerais.